PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PUBLIK DENGAN KEPUASAN PUBLIK SEBAGAI VARIABEL INTERVENING: PERAN NILAI PELANGGAN SEBAGAI MODERASI - Sefnedi Sefnedi (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2016)
This studyexamined the intervening effect of customer satisfaction on the relationship between service quality and customer loyalty and the role of customer value as moderating. The research population is all entire communities who received service quality of birth certificate issuance in the period of August-December 2014that accounted for 351customers and the numbers of usable samples were 187 customers.In order to test hypotheses, this study performs simple and hierarchical regression analyses. The results of analysis displayed that service quality positively influences customer satisfaction and customer loyalty, customer satisfaction was found to have positive effect on customer loyalty, customer satisfaction was proven as intervening variable on the relationship between service quality and customer loyalty, and customer value moderated the relationship between service quality and customer satisfaction. Keywords:Service Quality, Customer Satisfaction, Customer Value, and Customer Loyalty.